Analysis of the Starlink Satellite Network Filing Application - Wenhan YANG; Guoliang HUA; Yan FENG; Yuanfu LI; Ranran HOU (天地一体化信息网络)
The frequency and orbit requirements of Starlink were investigated and compared with the satellite network fi llings from SpaceX.And then the priority of SpaceX in the global frequency orbit resource competition was analyzed.Then, through interpreting the terms of the Radio Regulations that cited by SpaceX, the strategies, techniques and possible actions of SpaceX in application and modifi cation for satellite network fi llings were studied.The analysis results of this paper can provide reference for the network resources application and modifi cation work of low-orbit satellite Internet constellation in China.